Effect of process parameters on vertical forces and temperatures developed during friction stir welding of magnesium alloys. Issue 1 (July 2016) - Forcellese, A.; Martarelli, M.; Simoncini, M.
Abstract The effect of process parameters on vertical forces and temperatures developed during friction stir welding of AZ31 magnesium alloy sheets was widely investigated. To this end, friction stir welding (FSW) experiments were carried out with constant values of the rotational and welding speeds in the ranges from 1200 to 2500 rpm and from 30 to 100 mm/min, respectively. The influence of the time between the end of the sinking stage and the beginning of the welding one was also studied using dwelling time values ranging from 0 to 120 s. Vertical forces occurring during all stages of FSW were measured using a low-cost dynamometer developed by authors. Furthermore, temperatures in different positions of the welding line were monitored by means of K-type thermocouples. It was shown that during the dwelling stage, the vertical force decreases until a steady-state regime is reached. However, the dwelling time does not significantly affect the force value in the welding stage. The vertical force versus time curve promptly reaches a steady state during the welding stage. The force value rises with increasing welding speed and decreasing rotational speed; such effect is consistent with the one showed by rotational and welding speeds on temperature measured in different positions during FSW. Finally, forces and temperatures have been related to the mechanical properties of the joints. It was shown that both the ultimate tensile strength and ultimate elongation exhibit the highest values under the process parameters leading to the lowest vertical force and highest welding temperature.